Pengaruh Perubahan Suhu dan Tekanan Udara Terhadap Jumlah Koloni Kuman Pada Ruang Kamar Operasi RSUD Dr. Soetomo Surabaya - Budi Minarno; Yuly Peristiowati (Jurnal Imejing Diagnostik (JImeD), 2022)
Background: Hospital as one of the health facilities where health efforts are held. Health efforts are every activity to maintain and improve health, aiming to realize an optimal degree of health for the community. The cause of the disease can be in the floor, air, medical and non-medical equipment, that's one of the priorities of the hospital is patient safety. The purpose of the study was to find out the effect of changes in temperature and air pressure on the number of bacterial colonies in the operating room of Dr. Soetomo Regional General Hospital Surabaya.Methods: Design observational research with a cross-sectional approach. The population of all operating room rooms in Dr. Soetomo Regional General Hospital Surabaya is 86 rooms. Sampled all 86 spaces with total sampling techniques. Independent variables are temperature and air pressure. The dependent variable is the number of germ colonies.Results: The results showed no effect on the effect of room temperature on the number of bacterial colonies in the emergency operating room. In this case the temperature standard used is Permenkes RI Number 7 of 2019 obtained the category of room temperature with a standard of 22-27oC (p = 0.221). However, there is an effect of room temperature on the number of bacterial colonies in the emergency operating room (p =0.009) in Kepmenkes Number 1204 / Menkes / SK / X / 2004 obtained the room temperature category with a standard of 19-24oC. There is an influence of air pressure on the number of bacterial colonies in the emergency operating room based on Decree No. 7 of 2019, namely p = 0.002 and Kepmenkes Number 1204 / Menkes / SK / X / 2004 which is p = 0.000.Conclusions: A simple indicator of pressure monitoring is the tape attached at each entrance of the operating room, relatively immobile so that the possibility of air pressure inside the operating room with outside is balanced, when it should be positive pressure.